Knowledge Contribution Determinants through Social Network Sites: Social Relational Perspective - Majali, Tha'er A.; Bin Bohari, Abdul Manaf (International Review of Management and Marketing, 2016)
The advancement of the social network sites have enabled individual to share and exchange information through online platforms. This relatively new form of information exchange, motivations of knowledge contribution only recently received have significant academic attention. Many studies have focused at the usage intention of SNSs by examining the factors that affect individual's engagement in such environment. Knowledge contribution behavior can be explained from the social relational perspective that emphasizes the public goods. However, based on literature there is a need for further investigation for determinants of knowledge sharing through SNSs. This paper focuses on the social relational factors as key motives of individual's engagement in online knowledge sharing behavior. The research model empirically tested with a sample of 426 members of Facebook users. The results in this study confirm that reciprocity and sense of community are significantly related to users' engagement in knowledge sharing behavior, whereas trust had shown no relationship. The implications for both researchers and practitioners are discussed. Keywords: SNSs, knowledge contribution, social relations factors. JEL Classifications: D85, L14